PENGEMBANGAN INSTRUMEN UNTUK MENGUKUR KOMPETENSI SOSIAL GURU BERBASIS GENDER EQUALITY AND SOCIAL INCLUSION (GESI) DI SEKOLAH INKLUSI - Tita Rosita; Devy Sekar Ayu Ningrum; Muhammad Rezza Septian; Sukinah Sukinah; Mutiara Tectonia Safitri (Universitas Tribhuwana Tunggadewi, 2024)
The social competence of teachers based on gender equality and social inclusion (GESI) in this research is the teacher's ability to communicate with children with special needs based on managing social dynamics and the teacher's framework for promoting social inclusion. The aim of this research is to create an instrument to measure teachers' social competence based on gender equality and social inclusion (GESI). The research method used is quantitative descriptive research. The development of the questionnaire in this study incorporates a measurement framework that provides a systematic method based on a combination of theoretical and psychometric approaches. The sample was 91 teachers who taught in four Bandung City State Elementary Schools. Based on the research results, data was obtained that the GESI-based social competency questionnaire consists of three aspects, namely attitudes towards inclusive education, empathy for students with special needs, and problem solving. The number of items in the questionnaire, namely 36 items, has met the standards of reliability, content validity, construct validity, and provides initial evidence for the use of the instrument with the aim of measuring the social competence of GESI-based teachers in inclusive schools.